How Engage Employee Implicates Customer-Oriented Behaviours? (A Study on Logistics Industry in Jakarta) - Nilasari, B. Medina; Zuita, Stevani Cristin; Utomo, M. Razka (Universitas Bangka Belitung, 2025)
This research analyzes the influence of High Commitment Work Systems (HCWS) on Work Engagement through Psychological Capital (Psycap) and its implications for Customer Oriented Behaviors. This is field research that uses purposive sampling method. The data analysis approach employs Structural Equation Modeling (SEM) utilizing the AMOS version 22. The findings indicate that High-Performance Work Systems (HPWS) had a positive effect on PsyCap and work engagement. Furthermore, PsyCap was found to have a significant positive impact on work engagement. The analysis confirmed that PsyCap mediated the relationship between HPWS and work engagement. Finally, work engagement was shown to positively influence customer-oriented behaviors. Previous studies did not further examine how the results of employee engagement can influence customer-oriented behavior. The novelty of this study is that employee engagement of delivery employees is associated with customer-oriented behavior. The logistics industry has rapidly evolved since the onset of the Covid-19 pandemic, coinciding with the surge of online businesses. Delivery employees are at the forefront of logistics industry, so customer-oriented employee behavior is an urgent matter, especially in the era of online business.